Dydaktyka przeciwko dydaktyce - Oskar Szwabowski, Oskar Szwabowski (Kultura-Społeczeństwo-Edukacja, 2018)
The paper elaborates on the concept of the didactics of immanence. Relying on the discussion contained in a text entitled “Polityczność dydaktyki” (“Politicisation of Didactics”), it differentiates between two types of didactics, one related to transcendence and the other to immanence. Using the theoretical accomplishments of Deleuze and Lewis, the author creates a plan to build an educational machine of war.